1995
DOI: 10.1007/s001010050131
|View full text |Cite
|
Sign up to set email alerts
|

Postoperatives bilaterales Kompartmentsyndrom der Unterschenkel nach ausgedehnten urologischen Eingriffen in Steinschnittlage

Abstract: We report two cases of compartment syndrome of the lower leg that occurred in male patients aged 62 and 57 years, respectively, after 10 and 12-h urological surgery in the lithotomy position. During sedation and mechanical ventilation creatine kinase (CK) activity of more than 8,000 U/l was found in both patients. After extubation, clinical symptoms of the compartment syndrome were found. On the 1st day after surgery patient 2 underwent fasciotomy of both lower legs (Fig. 2). No lasting neurologic defects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The maximum safe time length of the operation has not been clearly known, but it was reported that the compartment syndrome occurred after more than 4 hours of operation by Warner and Martin [9], 10-12 hours of operation by Lampert et al [10], and 13 hours and 15 minutes of operation by Kumamato et al [11]. These risk factors were not involved in the case report herein, but the operation took 6 hours and 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum safe time length of the operation has not been clearly known, but it was reported that the compartment syndrome occurred after more than 4 hours of operation by Warner and Martin [9], 10-12 hours of operation by Lampert et al [10], and 13 hours and 15 minutes of operation by Kumamato et al [11]. These risk factors were not involved in the case report herein, but the operation took 6 hours and 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Since irreversible neuromuscular defects occur 12-24 hours after the operation [10], diagnosis is very important. Mar et al [15] reported that the pain is unreliable, as cardinal symptom and physical examination are also unreliable for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…CK values of over 2,000 U/l after surgery may be considered a warning sign in ventilated and sedated patients, in whom early clinical symptoms of the compartment syndrome such as pain and paresthesias cannot be assessed [50]. The presence of myoglobinuria suggests an impending CS but the amount of myoglobinuria does not correlate with the degree of underlying tissue injury [51].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of myoglobinuria suggests an impending CS but the amount of myoglobinuria does not correlate with the degree of underlying tissue injury [51]. Prophylactic use of mannitol may obviate the need for decompressive fasciotomy [41], however if myoglobinuria is established enforced diuresis is recommended in order to avoid renal complications [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, creatine kinase and lactate levels rise, due to muscle breakdown and anaerobic metabolism respectively. Creatinine kinase levels of > 2000 units/L can be a warning sign of compartment syndrome in a sedated and ventilated patient [65]. Similarly, ischaemia-modified albumin (IMA) has been shown to rise with reasonable sensitivity and specificity in the presence of critical limb ischaemia; however, its role in aiding the diagnosis of ACS remains unclear [66].…”
Section: Introductionmentioning
confidence: 99%